Effects of partial suckling on lactation performance of Galla and East African goats and the growth rates of the kids - Ruvuna, F.; Cartwright, T.C.; Okeyo Mwai, Ally; Muhuyi, W.; Ahuya, C.; Kitilit, J. (1984)
Experiments were conducted on East African (EA) and Galla (G) does to investigat the impact of different milking procedures on milk yield of does and the growth rate of kids. The procedures includes milking with absence or presence of kids and residual suckling milking half udder while kid suckling other half milking morning only and suckling all milk in the evening. Milking once a week in nascence of the kid and letting kid have access to all the milk. Milking in the presence of the kids increased does milk yield (60.4 kg) in 12 weeks perior, provided most milk for family consumption. Little milk was left to sustain proper growth of the kids, thus indirectly affecting their maturing rate. No milking procedure was proved to be superior, in all criteria used. There fore, there is a need to use an optimizing technique including socio-economic weights of milk for the family consumpion relative to the amount of milk for the family consumption relative to the amount of milk to sustain growth of the kids. Average daily milk yield of East African and Gall does were 335 and 409 g respectively. The average daily gain to 12 weeks of age under different milking procedure ranged from 0.49 g to 11. g.